(untitled) (Journal of Asian Development Studies, 2023)
The study aimed to assess national coaches’ knowledge, opinions, and practices regarding the perception of diet plans for young athletes in Pakistan. A sample of 45 national coaches was selected through a convenient sampling technique during Pakistan’s 33rd National Games. The researchers developed a Likert-type scale for the collection of data from respondents. The collected data were analyzed through the SPSS 20.0 version. As a result of the data analysis, no significant difference was found among the respondents regarding knowledge of diet for young athletes (p-value was .079, which is > 0.05). No significant difference was found among the respondents regarding coaches’ opinions about diet plans for young athletes (p-value was .091, which is > 0.05). No significant difference was found among the respondents regarding the current diet plan practice of young athletes (p-value was .086, which was > 0.05). Based on the analysis, the researchers recommend that the concerned authorities organize a diet awareness program and its role in sports performance.